Assessment of the role and value of frequency response support from wind plants - Teng,F; Strbac,G (IEEE Transactions on Sustainable Energy, 2016)
High penetration of wind generation causes concerns over frequency stability, as currently wind plants do not provide frequency response support. Extensive research has been conducted to investigate alternative designs of controllers to facilitate the provision of synthetic inertia and primary frequency response from wind plants. However, frequency response support from wind plants differs from that provided by conventional plants and its impact on the system's economic performance is not yet fully understood. In this context, this paper develops a novel methodology to incorporate the frequency response support from wind plants into generation scheduling, thus enabling the benefits of alternative control strategies to be quantified. Studies are carried out on the future Great Britain power system with different wind energy penetration levels and frequency response requirements. The impact of the uncertainty associated with the quantity of wind plants being online and the energy recovery effect are also analyzed. The results demonstrate that the benefits of frequency response support from wind plants may be significant, although these are system specific. The proposed model could also inform the development of grid codes, market mechanisms, and business cases associated with the frequency response support from wind plants.